Jamaica : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
Economic outcomes in Jamaica have fallen short of the authorities' objectives in recent years. As the government looks to reinvigorate its growth and debt reduction strategy, it is instructive to examine how exogenous shocks and other unanticipated developments can affect economic outcomes. First, it examines the impact on Jamaica's economy of external economic slowdowns and credit crunches. Second, it develops a framework to assess the probabilities of successfully reducing debt below pre-specified thresholds. Furthermore, the relationships that existed in the past may not hold in the future.